Optimization of liquid-liquid extraction of calcium with a serpentine microfluidic device. (January 2023) - Amini, Younes; Hassanvand, Amin; Ghazanfari, V.; Shadman, Mohammad Mahdi; Heydari, Mehran; Alborzi, Zahra Sayah
Abstract: In this work, novel solvent extraction and microfluidic technology were combined to separate and extract Ca 2+ ions. Subsequently, a serpentine microfluidic apparatus was used to separate calcium ions. By applying a flow regime map, a complete separation of aqueous and organic phases at the exit of the serpentine microfluidic device was achieved. The extraction performance through this technique was equal to 23.40% at a residence time of 4.2 s. For modeling and optimization, the Box-Behnken design approach (BBD) was applied to generate present data. The flow rate, pH, and DC18C6 concentration were the main variables of the aqueous phase. The data revealed that the extraction performance of Ca 2+ was 62.34%, and microfluidic extraction was 23.40% under the optimum conditions. The optimum operating conditions for the aqueous phase were the pH of 6.25, the DC18C6 concentration of 0.015 M, and the flow rate of the aqueous phase of 20 μl/min. Results indicated that the experimental efficiency and microfluidic extraction in the novel serpentine microchannel are higher than in similar studies in the same conditions. Highlights: Extraction efficiency of microfluidic device was modelled and optimized. Full phase separation was achieved at the end of the microchannel. %E and %Eeff in the new spiral microchannel are higher than the YY microchannel.